(untitled) (Research, Society and Development, 2023)
Objective: The objective of this study is to evaluate the quality of sleep in male individuals aged 20 to 59 years in a higher education institution. Methodology: The research method used was field research, with a quantitative and qualitative approach, using the epworth scale as a research tool and a self-assessment of sleep quality, carried out in a higher education institution, in Teresina-PI, with male individuals. Results: The sample consisted of 80% of young people between 20 and 29 years old, in which the double shift of study and work was relevant, which promotes a significant reduction in sleep time, contributing negatively to poor sleep quality. Conclusion: It was possible to conclude that there was a higher prevalence of poor quality sleep in individuals aged between 20 and 29 years, who study and work, and among brown people.